LITERATURE STUDY: IMPLEMENTATION OF CHEMISTRY LEARNING USING BLENDED LEARNING MODEL TO IMPROVE STUDENTS' HOTS (HIGHER ORDER THINKING SKILLS) - Badrus Syamsi; Ade Suryanda (Jurnal Eduscience, 2023)
This study aims to determine the effect of implementing chemistry learning using the blended learning model in increasing student HOTS. The method used in this research is literature study. The data collection technique used, namely collecting data by finding sources and creating them through primary sources such as books, journals and existing research. The results showed that learning chemistry using a blended learning model could increase students' HOTS. Chemistry learning using a blended learning model can shape students to study individually either in groups, face to face, or online, and to solve problems, identify, interpret, and communicate learning outcomes.